PERSONAL EXPERİENCES: PRACTİCAL APPROACHES AND METHODS FOR WORKİNG WİTH CHİLDREN ON THE AUTİSM SPECTRUM - Xaspoladov, Mensur (Health and Society, 2025)
This paper presents a comprehensive examination of the methods and practical experiences gained while working with children diagnosed with Autism Spectrum Disorder (ASD), specifically through the experiences of a case study involving a child named Ali. The research explores the impact of individualized interventions, dietary changes, and technological tools used in helping children on the autism spectrum develop social, emotional, and cognitive skills. By incorporating various interventions, we achieved significant progress in Ali’s development, which led to broader applications for other children diagnosed with ASD. The results emphasize the importance of personalized approaches and provide a potential roadmap for similar interventions in other communities. The study aims to contribute to the global discourse on autism treatment and research, particularly with regard to dietary interventions and the integration of technology (World Health Organization, 2024).